Analysis of the human development index in East Java Province 2017-2021 - Hartini, Debby Putri (Lembaga Riset, Publikasi dan Konsultasi JONHARIONO, 2024)
This research aims to determine Population, Education and Minimum Wages on the Human Development Index. The dependent variable is the Human Development Index, while the independent variables are Population, Education and Minimum Wage. The data used in this research is secondary data which examines data for 5 (five) periods 2017 – 2021 with Regencies/Cities in East Java Province. The research method used is panel data regression analysis. The tool used to carry out testing is Eviews 9. The tests used in this research are the FE, CE, RE, Chow, Hausman and LM tests. The results of this research are: 1) Population is significant and has a positive effect on the Human Development Index in the Regency/City of East Java Province, 2) Education is significant and has a positive effect on the Human Development Index. and 3rd) Minimum Wage has a significant negative effect on the Human Development Index.